The Transformation of the Meaning of Arabic Words in Indonesian: A Semantic Study of Loanwords and Islamic Concepts in Society - Khaerul Muttakin; Ahmad Ryadussolihin; Elfira Yunita Sapitri; Ilham Dhya'ul Wahid (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to analyze the transformation of the meanings of Arabic words absorbed into Indonesian through a semantic analysis of lexicographical sources. The research employs a qualitative, literature-based approach, analyzing 23 Arabic loanwords listed in the Kamus Besar Bahasa Indonesia (Great Dictionary of the Indonesian Language) and comparing them with their original meanings in the Al-Munawwir dictionary. The analysis was conducted by classifying changes in meaning into narrowing, broadening, shifting, amelioration, and pejoration. The results show that Arabic loanwords undergo various semantic changes, including narrowing, broadening, shifting, amelioration, and pejoration. Most religious terms, such as fitrah, ibadah, syariat, and iman, have narrowed in meaning due to the institutionalization of religious practices. In contrast, terms such as hijrah and dakwah have broadened in meaning in line with developments in social discourse and the media. On the other hand, words such as bid‘ah and jihad show shifts and pejorative changes influenced by ideological contestation and public representation. These transformations in meaning shape a contextual and dynamic understanding of Islam, but can reduce normative concepts if not accompanied by adequate semantic literacy.